Compact low profile 5.8 GHz MPA for on-body applications - Siba Monther Yousif; Anwer Sabah Mekki; Ahmed Jumaa Lafta (Institute of Advanced Engineering and Science, 2023)
A compact microstrip patch antenna (MPA) with a T shape monopole technique is designed, simulated, and measured. By using fire retardant material (FR-4) as a substrate with a low profile, the proposed antenna is designed and simulated to be used for on-body biomedical applications. A center frequency of 5.78 is achieved with a gain of 11.78 dB and a matching impedance of -47.47 dB. A 1.48 W/Kg (10 gm) as a specific absorption rate (SAR) is achieved and 29.69 dB front to back ratio with a bandwidth of 3.376 GHz. The antenna was examined in free space as well as on-body using CST-MW software. The proposed antenna is fabricated and examined. Finally, a comparison is done among simulated results, measured results, and the dual-band dual-mode antenna. The proposed antenna overcomes the latter work in terms of small size, high matching impedance, high front to back ratio, and operating bandwidth.